Evaluation of the efficiency of social intelligence development training in persons with alcohol dependence - L. A. Tursunkhodzhaeva; L. T. Baymirova (Лечащий Врач, 2021)
125 suffering from the middle stage of alcohol dependence patientshave been examined using the «Methods for the Study of Social Intelligence» by J. Guildford and M. Sullivan, adapted by E.S. Mikhailova. 82,4% of them have low indicators of the level of certain abilities development in the social intelligencestructure, which can complicate their social adaptation after treatment. In order to improve social adaptation, a training program aimed at developing the weaknesses of social intelligencehas been developed. The developed program based on a model of group psychotherapy in small groups. The main components of the program were the following: development of the ability to foresee the consequences of one's own behavior and the behavior of other people in a certain situation; to understand non-verbal reactions and the meanings of the same type of verbal reactions of a person; and to understand the logic of the situation of interaction with other peopledepending on the characteristics of the situation. The objectives of the training also included the development of the ability to empathy, decrease in the level of alexithymia, an increase in the level of self-regulation and resistance to social factors that contribute to the breakdown of remission, and relapse of alcohol dependence. The training conducted in a group of 8-12 people and divided on10 sessions of 2-2,5 hours each. Evaluation of the effectiveness of the training was made after its realization in three groups, and the comparison group consisted of alcohol-addicted patients who underwent a two-month program of medical and social rehabilitation. The analysis of the developed training effectiveness program results showed that the level of social intelligence development are comparable to the results of a two-month program of inpatient medical and social rehabilitation, and sometimes they were higher.